2020
DOI: 10.3390/antibiotics9020078
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Antimicrobial Activity of the Teleost Chemokine CXCL20b

Abstract: Fish are a potential source of diverse organic compounds with a broad spectrum of biological activities. Many fish-derived antimicrobial peptides and proteins are key components of the fish innate immune system. They are also potential candidates for development of new antimicrobial agents. CXCL20b is a grass carp (Ctenopharyngodon idella) CXC chemokine strongly transcribed at the early stage of bacterial infections, for which the immune role had not been reported to date. In the present study, we found that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The cationic and amphipathic properties of APMs contribute to the antimicrobial function (21). By contrast, CiCXCL20b, a homolog of CiCXCL20a, owns a bactericidal activity (10), exhibits cationic patchy surface and amphipathic structure (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cationic and amphipathic properties of APMs contribute to the antimicrobial function (21). By contrast, CiCXCL20b, a homolog of CiCXCL20a, owns a bactericidal activity (10), exhibits cationic patchy surface and amphipathic structure (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Expression and purification of CXCL20 members were performed as described previously (10). Briefly, sequences encoding CiCXCL20a, CiCXCL20b, and DrCXCL20 were inserted into pET-32a and transformed into E. coli BL21(DE3) TrxB (Invitrogen) to produce fusion protein, respectively.…”
Section: Expression and Purification Of Rcxcl20 Membersmentioning
confidence: 99%
See 1 more Smart Citation
“…We list the most recent findings within functional chemokine research. It has been shown that grass carp cxcl20b possessed antibacterial activity by attaching to the bacterial membrane (Xiao et al 2020). In another study, it was shown that common carp Cxcb1 stimulated neutrophil extracellular trap formation-which was suggested to be an antipathogenic event (Pijanowski et al 2020).…”
Section: Chemokines and Their Receptorsmentioning
confidence: 99%
“…CXCL11.3 and CXCL20.3 were two potential molecular markers for ESC resistance after ESC infection, while CXCL20.2 was suggestive as a molecular marker for columnaris infection 88 . Recently, CXCL20a/b in grass carp ( Ctenopharyngodon idella ) has been demonstrated to have potent antimicrobial activity in vitro and in vivo , and oral administration of CXCL20a nanopeptide can efficiently prevent bacterial infection in fish 89–91 . Such diversity in chemokine molecules may provide enriched resource for discovery of new AMPs and attract more interest towards exploration of this gene family as immune regulators.…”
Section: Categories and Properties Of Catfish Ampsmentioning
confidence: 99%